Biomimetic Synthesis of Rhytidenone A and Mode of Action of Cytotoxic Rhytidenone F. Issue 10 (27th January 2020) - Yue, Zongwei; Lam, Hiu C.; Chen, Kaiqi; Siridechakorn, Ittipon; Liu, Yaxi; Pudhom, Khanitha; Lei, Xiaoguang
Abstract: The rhytidenone family comprises spirobisnaphthalene natural products isolated from the mangrove endophytic fungus Rhytidhysteron rufulum AS21B. The biomimetic synthesis of rhytidenone A was achieved by a Michael reaction/aldol/lactonization cascade in a single step from the proposed biosynthetic precursor rhytidenone F. Moreover, the mode of action of the highly cytotoxic rhytidenone F was investigated. The pulldown assay coupled with mass spectrometry analysis revealed the target protein PA28γ is covalently attached to rhytidenone F at the Cys92 residue. The interactions of rhytidenone F with PA28γ lead to the accumulation of p53, which is an essential tumor suppressor in humans. Consequently, the Fas‐dependent signaling pathway is activated to initiate cellular apoptosis. These studies have identified the first small‐molecule inhibitor targeting PA28γ, suggesting rhytidenone F may serve as a promising natural product lead for future anticancer drug development. Abstract : Taking action : The biomimetic synthesis of rhytidenone A was achieved by a Michael reaction/aldol/lactonization cascade in a single step from the proposed biosynthetic precursor rhytidenone F. Moreover, the highly cytotoxic rhytidenone F was shown to target PA28γ, leading to the accumulation of p53, which is an essential tumor suppressor in humans, ultimately initiating cellular apoptosis. Rhytidenone F may serve as a promising natural product lead for future anticancer drug development.